Pelatihan Manajemen Produksi untuk Meningkatkan Kualitas Produk Rengginang Opak Dapur Inaq Muhid - Adil, Ahmat; Muhid, Abdul; Anggriani, Rini; Indrayanto, Georano; Tilani, Dianisa (LPPM Universitas Bumigora, 2024)
Several problems faced by Micro, Small and Medium Enterprises are the weak of knowledge and quality of human resources, and production tools, which are still very traditional. The aim of this service is to assist the small entrepreneur to solve their real problems used Training Problem Solving for Rengginang Opak Micro, Small and Medium Enterprises in central Lombok. The method used in this service is a descriptive qualitative method. In this method, to realize the implementation of activities, it is carried out several stages, starting from preparation by holding meetings and discussions related to the initial conditions of the partners, then the results of the initial meeting, the implementers conduct production management training for partners and the final stage evaluates the community service activities. The result of this service activity is an increase in production quality which can be seen from the increased management capability of Rengginang Opak managers. Furthermore, the quantity and quality of the products produced become increasingly varied in terms of size and taste, The society can package the production to be better so that they can compete in the national market. The impact of this activity is the society has additional financial support from the business.